2011
DOI: 10.1673/031.011.14401
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Range of Honey Bees,Apis mellifera, in Alfalfa Seed Production Fields

Abstract: A study was conducted in 2006 and 2007 designed to examine the foraging range of honey bees, Apis mellifera (Hymenoptera: Apidae), in a 15.2 km2 area dominated by a 128.9 ha glyphosate-resistant Roundup Ready® alfalfa seed production field and several non-Roundup Ready alfalfa seed production fields (totaling 120.2 ha). Each year, honey bee self-marking devices were placed on 112 selected honey bee colonies originating from nine different apiary locations. The foraging bees exiting each apiary location were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 18 publications
4
74
0
1
Order By: Relevance
“…Generalist insects including native and introduced bees are known to routinely fly distances of several kilometres, especially among fragmented habitat (Dick, 2001;Jha and Dick, 2010;Hagler et al, 2011) and may directly facilitate pollen dispersal when traversing intervening unsuitable habitat among populations. Pollen dispersal over a distance of 1.6 km has also been recorded previously for A. saligna, a common widespread species of the more mesic areas of south west WA, using direct paternity analysis methods (Millar et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Generalist insects including native and introduced bees are known to routinely fly distances of several kilometres, especially among fragmented habitat (Dick, 2001;Jha and Dick, 2010;Hagler et al, 2011) and may directly facilitate pollen dispersal when traversing intervening unsuitable habitat among populations. Pollen dispersal over a distance of 1.6 km has also been recorded previously for A. saligna, a common widespread species of the more mesic areas of south west WA, using direct paternity analysis methods (Millar et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…A radius of 5 km was found as the main foraging distance, accounting for 90% of the foraging activity (Visscher and Seeley, 1982). Hagler et al (2011) found that the foraging distance of honey bees ranged up to 5.983 km. Based on these findings, we decided to look for relationships between land use and colony losses within radii of 2 km and 5 km around the apiaries as estimates of the mean and main foraging distances.…”
Section: Data Analysesmentioning
confidence: 95%
“…It was measured in ArcGIS 10.0 software (upon Corine Land Cover 2006 data) as ratio of all forests over a 5.5-km radius around the populations. The distance used here was assumed to be a reasonable length to overcome a common pollinator like honey bees (Beekman and Ratkiens 2000;Hagler et al 2011). The O COV represents possible habitats for S. myrsinifolia and better conditions for pollinator movement.…”
Section: Aflp Procedures and Data Treatmentmentioning
confidence: 99%